Beras pratanak, Mutu, Steaming, Pengaruh Variasi Steaming Time Terhadap Mutu Fisik dan Sensorik Dari Beras Pratanak Pada Padi Varietas Lokal di Kabupaten Aceh Tengah: Pengaruh Variasi Steaming Time Terhadap Mutu Fisik dan Sensorik Dari Beras Pratanak Pada Padi Varietas Lokal di Kabupaten Aceh Tengah - irwansyah irwan; Syahirman Hakim; Muhammad Zulfikar Nasuution; Syifa Saputra; Rustam Efendi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
The steaming process is one of the stages a make parboiled rice process that produces brown rice. Brown rice is one of the foods widely consumed because it is healthy. This study aims to determine the analysis of the The steaming process is one of the stages of the parboiled rice process that produces brown rice. Brown rice is one of the foods widely consumed because it is healthy. This study aims to determine the analysis of the physical, chemical, and sensory properties of parboiled rice quality resulting from steaming treatment in Central Aceh Regency. The research method used is descriptive with steaming treatment at 90°C with steaming time treatment of 20 minutes, 25 minutes, and 30 minutes. Based on the results of physical tests, the physical quality of the rice head is 62.5% in the steaming treatment at 90°C with 30 minutes including medium rice quality 3 based on SNI Rice 6128: 2015. The higher the percentage of head rice yield, a lower on percentage of broken rice and rice grits. Based on the results of chemical tests, brown rice has nutritional content such as fat content, protein content, and high carbohydrate content than brown rice processed without steaming treatment. Based on the sensory test of parboiled rice by panelists, overall, the color, texture, taste, and aroma were assessed, namely steaming at a temperature of 90°C for 30 minutes with a liking category of 6.49. The effect of temperature and time during steaming on parboiled rice can affect quality and sensory.